Smartphone Addiction and Its Psychological Consequences among University Students in Pakistan - Haadia Hidayat; Aqsa Waqar; Asaad; Qurat Ul Ain Sammar; Nusrat Jabeen; Zaib Samraz (Indus Journal of Social Sciences, 2025)
Background: Negative psychological outcomes, particularly among college students, have been linked with excessive smartphone use. Over-dependence on smartphones can result in emotional upheaval which can lead to unsatisfactory academic achievement not to mention overall wellbeing. Aim: The objective of this study is to assess the impact of smartphone addiction on depression, anxiety, and stress level among students of varying faculties and institutions in the country. Method: A cross-sectional descriptive study was conducted on 400 students from four major universities in Pakistan. The smartphone dependency was assessed using SAS (Smartphone Addiction Scale) while the psychologic distress was measured with DASS-21 (Depression Anxiety Stress Scales). The survey conducted was cross sectional and the analysis was conducted by correlation analysis and ANOVA to find out relationships or differences between groups. Results: The results showed that smartphone addiction is significantly positively correlated to depression (r = .68, p < .001), anxiety (r = .63, p < .001), and stress (r = .60, p < .001). The higher the smartphone addiction levels, the increased psychological distress one faces. In all three areas, the students from Karachi were found to have greater smartphone addiction and more psychological distress than students from other cities. Students of computer science and engineering reported high levels of smartphone addiction and advanced psychological distress compared to inline Medical or Law students. Conclusion: The overuse of smartphones is a major contributing factor to emotional problems suffered by university students. To reduce irritation and aid in achieving digital wellness, specific initiatives, ‘detox’ programs, and information awareness campaigns should be prioritized.